A Case of Invasive Gastrointestinal Mycotypha Infection in a Patient with Neutropenia - Polina Trachuk; Wendy A. Szymczak; Peter Muscarella; Uzma N. Sarwar (Case Reports in Infectious Diseases)
Gastrointestinal mucormycosis is a rare life-threatening infection to which neutropenic patients are especially vulnerable. Mycotypha microspora is a mucormycete that has not been described as a human pathogen. We discuss the successful eradication of gastrointestinal Mycotypha microspora in a neutropenic patient with simultaneous pulmonary Aspergillus fumigatus infection.